Peran Positif Kegiatan Ekstrakurikuler di Lingkungan Sekolah Dasar Bagi Peserta Didik (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Extracurriculars are guidance, counseling, interests, abilities and potential of students which are held outside of learning hours carried out by the teacher. Schools provide a forum for extracurricular activities as a form of channeling interests, skills and creativity. Extracurricular activities in elementary schools can have a positive impact on students within the school environment, such as increasing students' creativity, improving students' character and training students' social interactions within the school environment. The method used in this research is the literature review method. Based on the type of data collected from various sources to form this article. The library study method is a method used to collect data by understanding the theories of various journals, books and articles that are interconnected in research.